Population Growth: An Emerging Crisis on Water Availability - Koirala, Madan (Tribhuvan University Journal, 2010)
Not available. Key words: Population Growth; Crisis on water; Nepal Tribhuvan University Journal Vol. XIX, 1996 Page: 33-38 Uploaded Date: 22 Nov., 2010